2016
DOI: 10.1209/0295-5075/116/18003
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function clustering in multiplex brain networks

Abstract: A key question in neuroscience is to understand how a rich functional repertoire of brain activity arises within relatively static networks of structurally-connected neural populations: elucidating the subtle interactions between evoked 'functional connectivity' and the underlying 'structural connectivity' has the potential to address this. These structural-functional networks (and neural networks more generally) are more naturally described using a multilayer or multiplex network approach, in favour of standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…The novel multilayer framework provides a unique opportunity to study, simultaneously, structural and functional information, and, in fact, it has been recently used for this purpose [59,60]. …”
Section: Structural and Functional Decompositionmentioning
confidence: 99%
“…The novel multilayer framework provides a unique opportunity to study, simultaneously, structural and functional information, and, in fact, it has been recently used for this purpose [59,60]. …”
Section: Structural and Functional Decompositionmentioning
confidence: 99%
“…In the case of the model organism C. elegans, a multilayer network with alternative modes of interaction (synaptic, gap junction, and neuromodulator) between neurons has been introduced [23,24], allowing for a better understanding of aminergic and peptidergic modulation of behaviour [25]. Anatomical and functional information has been integrated to gain insights about the macro-scale topology of the Macaque monkey [26] and the human brain [27]. Temporal [28,29] and multi-frequency [30,31,32,33] decompositions of human brain activity, followed by their successive integration into multilayer networks, have been used to improve our understanding of brain function in cognitive tasks and brain diseases, such as Alzheimer's, Parkinson's or Schizophrenia.…”
Section: Connectomicsmentioning
confidence: 99%
“…Previous research on dementia state classification showed that using multilayer networks (i.e., stacking different networks) improved the prediction accuracy for disease identification when compared with using single-view networks (Crofts et al, 2016;Giuliano Zippo and Castiglioni, 2016;La Rocca et al, 2017). However, none of these multilayer network-based methods explored the relationship between two consecutive layers in the network or cortical morphology (Brown and Hamarneh, 2016).…”
Section: Introductionmentioning
confidence: 99%